Patient Perceptions And Expectations Regarding Satisfaction With Online Outpatient Registration Services At Karangasem Regional General Hospital (RSUD Karangasem) - Ni Kadek Sulastri; I Made Sudarma Adiputra; Nurul Faidah (International Journal of Health Engineering and Technology, 2026)
The advancement of digital systems in healthcare has prompted hospitals to implement online registration systems to enhance service effectiveness, reduce waiting times, and improve patient satisfaction. However, implementation challenges persist, such as scheduling mismatches for follow-up visits, data verification issues, and the need for patients to queue again at the registration counter. This study aims to examine patient perceptions and expectations regarding satisfaction with the outpatient online registration service at RSUD Karangasem. A qualitative method with a descriptive approach was employed, utilizing purposive sampling with nine participants. Data were collected through interviews and observations, using interview guides and observation sheets as research instruments. Interview data analysis involved data reduction, data presentation, and conclusion drawing. The results indicate that patient perceptions of the online registration system are generally positive due to the convenience, time efficiency, and flexibility it offers. Nevertheless, obstacles remain, including network disruptions, system errors, and suboptimal supporting facilities. These conditions create a gap between patient perceptions and expectations; patients desire a system that is more stable, fast, and accurate. In conclusion, while the outpatient online registration system at RSUD Karangasem has provided benefits, it has not yet fully met patient expectations. Therefore, continuous improvement of the system and supporting facilities is necessary to enhance patient satisfaction.